Exascale applications: skin in the game. (20th January 2020) - Alexander, Francis; Almgren, Ann; Bell, John; Bhattacharjee, Amitava; Chen, Jacqueline; Colella, Phil; Daniel, David; DeSlippe, Jack; Diachin, Lori; Draeger, Erik; Dubey, Anshu; Dunning, Thom; et al.
Abstract : As noted in Wikipedia, skin in the game refers to having 'incurred risk by being involved in achieving a goal', where ' skin is a synecdoche for the person involved, and game is the metaphor for actions on the field of play under discussion'. For exascale applications under development in the US Department of Energy Exascale Computing Project, nothing could be more apt, with the skin being exascale applications and the game being delivering comprehensive science-based computational applications that effectively exploit exascale high-performance computing technologies to provide breakthrough modelling and simulation and data science solutions. These solutions will yield high-confidence insights and answers to the most critical problems and challenges for the USA in scientific discovery, national security, energy assurance, economic competitiveness and advanced healthcare. This article is part of a discussion meeting issue 'Numerical algorithms for high-performance computational science'.